Evaluadores de este Número (RUNA, archivo para las ciencias del hombre, 2016)
Evaluadores NacionalesElisa Cragnolino, Universidad Nacional de CórdobaAndrés Dimitriu, Universidad Nacional del ComahueEva Lamborghini, Universidad de Buenos AiresAndrea Mastrangelo, Universidad Nacional de San MartinPaola Carolina Monkevicius, Universidad Nacional de La PlataBrígida Renoldi, Universidad Nacional de MisionesAlejandro Roig, Universidad Nacional de San MartinEsteban Serrani, Universidad Nacional de San MartinAlicia Szmukler, Facultad Latinoamericana de Ciencias sociales (FLACSO) sede ArgentinaLia de la Vega, Facultad de Ciencias Sociales, UNLZ / UNLaMNicolás Viotti, Facultad Latinoamericana de Ciencias sociales (FLACSO) sede Argentina Evaluadores ExtranjerosGabrie Angelotti, Universidad Autónoma de Yucatán, MéxicoJuan Antonio Flores Martos, Universidad de Castilla - La Mancha, EspañaLaura Cecilia López, Universidade do Vale do Rio dos Sinos, BrasilPablo Neder, Centro Nacional de Investigaciones Científicas (CNRS), Francia.Elsie Rockwel, Centro de Inv. y de Estudios Avanzados del Instituto Politécnico Nacional, MéxicoLuiz Fernando Rojo, Universidad estadual de Rio de Janeiro, BrasilMaría Catarina Zanini, Universidade Federal de Santa Maria, Brasil